Wealth tax: perspectives in a post-pandemic world - Pedro Humberto Bruno de Carvalho Junior; Fabio Veras Soares (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
Many studies have shown that wealth inequality is even greater than income inequality and has increased in recent decades. This issue of Policy in Focus is dedicated to wealth taxes, presenting various perspectives on whether they can be an effective instrument for distributive and fiscal policies to promote a more inclusive recovery in a post-COVID-19 pandemic world.
Keywords: 330; wealth tax; COVID-19 pandemic; inclusive growth